Sonographic characteristics of the placenta, uterine wall, and placentomes during pregnancy in cows - Zoller, Doreen; Peterson, Susanne; Boos, Alois; Hässig, Michael; Bleul, Ulrich (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2019)
Objective In human medicine, contrary to bovine medicine, close monitoring of risk pregnancies is an integral part of obstetrics. A prerequisite for this is the knowledge of the normal findings during pregnancy.Material and methods For this purpose serial transrectal sonographic examination of the placentomes, uterine wall, and fetal membranes were carried out in 24 healthy (mean age 8.1 ± 3.7 years, Brown Swiss [n = 21], Red Holstein [n = 2], Simmental [n = 1]) cows from week 6 to 43 of gestation. An 8-MHz linear transducer was used to assess the thickness and appearance of the endometrium and myometrium, the height and width of placentomes, the thickness of the uterine wall including the adjacent chorion laeve (combined thickness of uterus and placenta, CTUP), and the echogenicity of the fetal fluids. The uterine wall and the placentomes were measured in 4 different zones of both uterine sides including a zone near the cervix, at the corpus near to the bifurcation, at the middle, and near the tip of the uterine horn.Results Placentome height and width were closely correlated with gestational age (height: r = 0.78; width: r = 0.83; both p < 0.0001). Placentome size increased progressively in all uterine zones until week 27, after which time their growth slowed until week 31 and then plateaued until parturition. Placentomes in the fetus-bearing horn were larger than in the non-fetus-bearing horn (p < 0.01) and were significantly smaller (height and width) near the tip of the horn than in the other 3 zones (p < 0.001 to < 0.01). The mean thickness of endometrium and myometrium, myometrium at the base of the placentome, and the mean CTUP did not change significantly during gestation. The echogenicity of the allantoic fluid did not change, but the amniotic fluid became more echogenic during gestation (p < 0.0001).Conclusion and clinical relevance Sonographic examination of placentomes and amniotic fluid are a promising diagnostic tool for the estimation of the duration of bovine pregnancies and for diagnosing possible complications.
Keywords: Placentometry; CTUP; gestation; bovine